Modeling of geophysical fluid flows: case of a Peruvian region - Rubio Mercedes, Obido (2021)
We model mathematically and computationally the geophysical fluid flows, using the basic concepts of rational mechanic and mathematical analysis; then as applications we present the numerical simulation of a rotating of viscoelastic fluid flow and simulate the forecast of some atmospheric variables for the region of La Libertad-Peru, using the Brazilian Regional Atmospheric Modeling System BRAMS; some climate variable as the precipitation is verify again the observed variable. Since its height above sea level varies from 3 msnm to 4800 msnm, observes certain instabilities in the simulation mainly when using a high-resolution mesh, due to this situation we try to improve stability by introducing a monotonic convective scheme of Walce, which is a high order and stable scheme.